2006
DOI: 10.2807/esw.11.07.02900-en
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax in animals and a farmer in Alto Adige, Italy

Abstract: Between 21 and 29 December 2005, seven animals (1 bull, 1 cow, 1 sheep and 4 goats) died within 2 hours of becoming ill on a remote farm (1500 m above sea level) in Alto Adige, northern Italy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This conclusion was tentatively suggested during the epidemiologic investigation of this anthrax case (18 ), and we have confirmed that inference. Based on the HRMA and the MLVA25 analyses, we have assigned these 2 strains to B. anthracis cluster B3.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…This conclusion was tentatively suggested during the epidemiologic investigation of this anthrax case (18 ), and we have confirmed that inference. Based on the HRMA and the MLVA25 analyses, we have assigned these 2 strains to B. anthracis cluster B3.…”
supporting
confidence: 73%
“…We applied HRMA initially to a B. anthracis collection at the Istituto Superiore di Sanità, Rome, Italy. This collection consists of 12 strains-10 previously analyzed with MLVA25 and 2 new isolates of a B. anthracis strain involved in a recent case of human anthrax in Italy (18 ). One of these latter isolates was from necropsy materials from a sheep killed by anthrax, and one was isolated from the shepherd's cutaneous lesion.…”
mentioning
confidence: 99%
“…Local knowledge of anthrax is vastly improved [ 10 - 12 ]. In recent years, outbreaks have been recorded in the Northeastern [ 13 ] and Northern [ 14 ] regions of Italy. Unfortunately, because of the ephemeral cycles of this disease, it is not always possible to establish the full extent of anthrax distribution in specific regions.…”
Section: Introductionmentioning
confidence: 99%
“…Regional and local health care units have done their due diligence on it and emergency and intensive care units should be ready to diagnose and treat even the pulmonary forms. A recent outbreak of natural anthrax has shown a valid integrated response to control it [ 14 ] . Small attacks would be faced similarly.…”
Section: Anthraxmentioning
confidence: 99%